Role of 18F-FDG PET/CT in the diagnosis and management of multiple myeloma and other plasma cell disorders: a consensus statement by the International Myeloma Working Group - Cavo, Michele; Hillengaß, Jens; Goldschmidt, Hartmut (The lancet. Oncology, 2017)
Summary The International Myeloma Working Group consensus aimed to provide recommendations for the optimal use of 18fluorodeoxyglucose (18F-FDG) PET/CT in patients with multiple myeloma and other plasma cell disorders, including smouldering multiple myeloma and solitary plasmacytoma. 18F-FDG PET/CT can be considered a valuable tool for the work-up of patients with both newly diagnosed and relapsed or refractory multiple myeloma because it assesses bone damage with relatively high sensitivity and specificity, and detects extramedullary sites of proliferating clonal plasma cells while providing important prognostic information. The use of 18F-FDG PET/CT is mandatory to confirm a suspected diagnosis of solitary plasmacytoma, provided that whole-body MRI is unable to be performed, and to distinguish between smouldering and active multiple myeloma, if whole-body X-ray (WBXR) is negative and whole-body MRI is unavailable. Based on the ability of 18F-FDG PET/CT to distinguish between metabolically active and inactive disease, this technique is now the preferred functional imaging modality to evaluate and to monitor the effect of therapy on myeloma-cell metabolism. Changes in FDG avidity can provide an earlier evaluation of response to therapy compared to MRI scans, and can predict outcomes, particularly for patients who are eligible to receive autologous stem-cell transplantation. 18F-FDG PET/CT can be coupled with sensitive bone marrow-based techniques to detect minimal residual disease (MRD) inside and outside the bone marrow, helping to identify those patients who are defined as having imaging MRD negativity.
Gesehen am 04.05.2018